Penguatan Literasi Keuangan Syariah sebagai Pilar Keberlanjutan UMKM di Sumbergempol - Sari, Citra Mulya; Huda, Qomarul; Tegar, Tegar (Jurnal Pengabdian pada Masyarakat Ilmu Pengetahuan dan Teknologi Terintegrasi, 2024)
Effective financial management is one of the key factors for business sustainability, especially for MSMEs. However, many MSMEs in Sumbergempol, Tulungagung face challenges in developing a sharia-based financial plan. The main problems include a lack of understanding of sharia financial principles, such as riba, gharar, and maysir, as well as limited skills in budgeting and separating personal finances from business finances. To address these issues, the community service team from the Faculty of Islamic Economics and Business at UIN Sayyid Ali Rahmatullah Tulungagung conducted a "Sharia Financial Planning Training" program over three days on October 12, 13, and 20, 2024. The implementation method consisted of three main stages, namely participant socialization and mapping, Focus Group Discussion (FGD), and reflection sessions. Through this activity, participants were provided with theoretical and practical materials on sharia-based financial planning, budgeting, and cash flow management. The results of the activity showed an increase in participants' understanding and skills in managing business finances according to sharia principles. Participants were able to separate personal finances from business finances, create budget plans, and develop more effective financial strategies. This activity also fostered collaboration among MSME actors and strengthened their motivation to apply sharia principles in their businesses. Moving forward, it is proposed to conduct follow-up training and intensive mentoring to strengthen the sustainable implementation of sharia financial planning.